Shrinking of Cities in the Czech Republic and its Reflection on Society: Case Study of Karviná City - Šerý, Ondřej; Svobodová, Hana; Šilhan, Zdeněk; Szczyrba, Zdeněk (Geographica Pannonica, 2018)
The shrinking of cities is a process that accompanies cities in post-conjunctural changes, when they are entering a phase of economic decline and the decline in population connected with it. The Ostrava-Karviná area is one of the economically problematic regions in the Czech Republic nowadays but it used to be ranked as one of the economic heartlands in the period of socialism. The region, dependent on bituminous coal mining and heavy industry, gradually began to decline after the year 1989 and one of the consequences is a significant decline in its population. This paper deals with identification of the causes and consequences of shrinking cities explained through the example of the town of Karviná through an analysis of quantitative data, questionnaire surveys, and semi-structured interviews. The questionnaire survey revealed that the main reason causing the departure of young and educated citizens is the lack of work opportunities. High unemployment and thus the presence of many socially disadvantaged people causes the atmosphere in the city to deteriorate, and this is accompanied by social problems, such as ageing of the population or criminality. Lack of safety of citizens and a bad environment are other reasons why young people leave the city. The decreasing number of citizens closes the vicious circle by leading to a lower demand for services, closing of shops and other services and increasing numbers of empty houses and flats. Another essential part of the paper is the question of possible measures by the local authority leading to the elimination of these undesirable phenomena, but also the belief in the necessity of help from the government.